2004
DOI: 10.1088/1126-6708/2004/12/047
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Equations from a First-Order Perturabtive Superspace Formulation of 10D, N=1 String-Corrected Supergravity

Abstract: Utilizing a first-order perturbative superspace approach, we derive the bosonic equations of motion for the 10D, N = 1 supergravity fields. We give the Lagrangian corresponding to these equations derived from superspace geometry. Moreover, the equivalence of this Lagrangian to the first-order perturbative component level Lagrangian of anomaly-free supergravity is proven. Our treatment covers both the two-form and sixform formulations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…In our previous work, [1], we found a candidate for the so called X tensor as discussed in [2]. This along with other techniques, enabled a solution to be found to second order.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous work, [1], we found a candidate for the so called X tensor as discussed in [2]. This along with other techniques, enabled a solution to be found to second order.…”
Section: Introductionmentioning
confidence: 90%
“…We followed the perturbative approach of Gates et al [2,3,5]. This group found a consistent solution to the Bianchi identities in superspace, thereby constructing a manifestly supersymmetric theory, achieving this to first order in γ, [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our starting point will be the Bianchi identities as listed in [5]. The sigma matrix identities and symmetries are recorded in [3].These geometrical methods nowadays are known as deformations [1], and the constraints have sometimes been referred to in the past as beta function favored (βF F ) constraints [7] (see for related subjects e.g. [8]).…”
mentioning
confidence: 99%
“…It must be observed that there are two independent spacetime spinors in the Type II sigma-model, so one has two independent fermionic structure groups. Thus, 1 Actually, they carry indices W and X , respectively, which is omitted. field strengths and T , R are the supertorsions and supercurvatures; It was shown in [8] that the N=(2,2) structure of the hybrid formalism selects a different version of the N=2 Poincaré Supergravities described in [11].…”
mentioning
confidence: 99%